Ornamenta urbana in the finis terrae: Some Observations on Elites and Luxury Elements in the Roman Villas of Northwest Hispania - Piay Augusto, Diego (Ktisis – Journal of Late Antique Housing, 2025)
Late Antique literary sources attest to the presence of high-ranking individuals from late Roman society (4th–5th centuries) associated with the territory of the former province of Gallaecia. However, comprehensive studies evaluating the luxury elements documented in the villas of this region, particularly those linked to elite groups, remain absent. This gap is especially pronounced in the westernmost areas of Gallaecia, corresponding to the modern regions of Galicia and Asturias. This study begins by analysing the geographical boundaries of the ancient province of Gallaecia and the specific study area. Next, a brief prosopographical analysis will provide insight into which members of the elite may be linked to the Hispanic Northwest. The third section examines the study of villas in Galicia and Asturias. Finally, the presence of luxury elements in the villas of the study area will be analysed. The objective of this paper is, therefore, to compile all available evidence related to the presence of luxury items (mosaics, sculptures, wall paintings) in the villas in these regions in order to corroborate the presence of the elites mentioned in literary sources through archaeological analysis. A defining characteristic of the upper classes during Late Antiquity was their preference for high-quality products, which they procured for their opulent residences, even if these were located at the edges of the known world.